Sejarah Perkembangan Tarekat Naqsyabandiyah dalam Perspektif Pendidikan Islam di Pasaman Barat - Fitria, Mita (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The Naqshbandiyah order has been an integral part of the development of Islamic spirituality in Indonesia, particularly in West Pasaman, West Sumatra. This article explores its historical trajectory through the perspective of Islamic religious education, with a focus on prominent figures such as Syeikh Muhammad Said Padang Bubus and his descendants. Employing a qualitative descriptive approach, the study analyzes how the teachings of Sufism within this order contribute to the formation of spiritual character and religious education among the local community. The findings indicate that the spiritual charisma (karāmah) and practices of the syekh not only strengthened faith but also served as a model of holistic education that integrates spiritual dimensions with everyday life. The study concludes that the Naqshbandiyah order has played a significant role in shaping spirituality-based character education that remains relevant in the contemporary era.